Training in Lay-Up Shooting and Finger Roll Lay-Up Enhances Basketball Shooting Ability in Relation to Arm Muscle Strength in Upper Secondary School Students - Diputra, I Nyoman Yoga; Dharmadi, Made Agus (Jurnal Pendidikan dan Pengajaran, 2025)
Athletes still do not understand the importance of arm muscle strength during basketball training and have not mastered good shooting techniques, so the ball throw is still not optimal. This study aims to analyze the effect of lay-up Shooting and Finger roll lay-up Training on Basketball Shooting Ability in terms of Arm Muscle Strength in High School Students. The research method uses a quasi-experiment with a design factor. The study population was 60 high school students. Sampling used all existing populations. Data collection methods through tests and test recording. The quantitative data obtained were analyzed using two-way ANOVA with a treatment-by-level design assisted by the SPSS application. The study's results showed. First, there was a difference in shooting accuracy results in participants who received lay-up shoot technique training compared to finger roll layup. Second, there was an interaction between the lay-play-up shooting technique and finger roll lay-play-up with arm muscle strength, significantly affecting shooting accuracy. Third, a significant difference in shooting accuracy was found between the lay-up shooting technique and finger roll lay-up. Fourth, finger roll layuplayup provides more advantages in shooting accuracy than layup shoot because this technique relies more on finger control and agility, not just arm muscle strength. It is concluded that arm muscle strength and proper technique play an important role in improving basketball shooting accuracy.